“Entre Deux Transatlantiques”: American Religion and the French Family at the Comédie-Française (1890) - LeeAnn Broderick; Carter Charles; Corry Cropper (Transatlantica)
Mormonism, seen in 1865 by French critic Hippolyte Taine as an American religious and social experiment conducted “for our benefit,” appears frequently in French thinking in the second half of the nineteenth century. Whether Taine intended it or not in his use of the word “benefit,” this American religion was mobilized in French conversations about pressing sociopolitical issues such as gender identity, marriage, and the social norms surrounding those issues. Relying on a cultural studies approach, we illustrate in this article how French literary critic and playwright Philippe Gille uses Mormonism in Camille, a play in which he explores issues of gender in the context of the état civil during the Third Republic. First performed at the French national theater (Comédie-Française) in 1890, Gille’s play stages the transatlantic encounter of Franco-American cultures and values as a way to displace questions about the capacity of the French state to regulate marriage and family relationships.